Economic analysis for renewable electricity development with professional disaggregation: The case of Taiwan. (10th January 2021) - Wu, Kuei-Yen; Huang, Yun-Hsun; Wu, Jung-Hua
Abstract: The Taiwanese government has set an ambitious goal of increasing the penetration of renewable energy in the power sector from 4.8% in 2016 to 20% by 2025. The enormous investment required to achieve these goals is expected to have wide ranging economic benefits. For example, the move toward a green economy will create a large number of new jobs and provide additional economic stimulus through on-going development. This study employs the input-output method in conjunction with questionnaire surveys to elucidate these effects. The sectors that are expected to see the greatest economic benefits include iron/steel/miscellaneous metals, electrical equipment and mechanical equipment. The accumulated economic output is expected to increase by 5.89 trillion NTD; meanwhile, employment in renewable electricity sectors is expected to increase by 142 thousand jobs. Note that 51.90% of the job increment will be for professionals and technical specialists. At present, the cultivation of special skills is dependent on in-house training. Industrial parks specializing in renewable energy should be established to promote the exchange of talent and technological innovations. In the manufacturing sector, 55.55% will be for craft related workers and elementary labourers. These changes will necessitate a reorganization of the workforce through government-academia-industry cooperation.